2002
DOI: 10.1177/00238309020450030301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variation in Emotional Tone of Voice on Speech Perception

Abstract: The effects of variation from stimulus to stimulus in emotional tone of voice on speech perception were examined through a series of perceptual experiments. Stimuli were recorded from human speakers who produced utterances in tones of voice designed to convey affective information. Then, stimuli varying in talker voice and emotional tone were presented to listeners for perceptual matching and classification. The results showed that both intertalker variation in talker voice and intratalker variation in emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Hence the data of Experiment 1 would seem to indicate that the spectral differences introduced with changes in emotional prosody are beneficial to speech detection. As noted in our discussion of previous research (e.g., Mullennix et al, 2002), prosody will tend to have a greater range of frequency and intensity values when emotionally expressed, and those differences may have improved speech detection in the auditory conditions. While we used a corresponding face/voice emotionally expressive combination for our initial investigations, clearly there was an influence of the vocal prosody that needs to be isolated.…”
Section: Auditory Speech and Emotionmentioning
confidence: 57%
See 1 more Smart Citation
“…Hence the data of Experiment 1 would seem to indicate that the spectral differences introduced with changes in emotional prosody are beneficial to speech detection. As noted in our discussion of previous research (e.g., Mullennix et al, 2002), prosody will tend to have a greater range of frequency and intensity values when emotionally expressed, and those differences may have improved speech detection in the auditory conditions. While we used a corresponding face/voice emotionally expressive combination for our initial investigations, clearly there was an influence of the vocal prosody that needs to be isolated.…”
Section: Auditory Speech and Emotionmentioning
confidence: 57%
“…1. However, based on previous research, there is evidence that suggests that emotions may improve audibility by increasing spectral variation and speech segregation (Mullennix et al, 2002;Trainor et al, 2000). As such we completed separate analyses of the auditory-only and audiovisual speech, specifically testing the differences between emotions.…”
Section: Resultsmentioning
confidence: 99%
“…Even though listeners can apparently cope with such situations (e.g., Ladefoged & Broadbent, 1957;Syrdal & Gopal, 1979), perceptual normalization is not cost-free (Mullennix et al, 1989(Mullennix et al, , 2002Nakai, 2013;Sommers et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Mullennix et al (2002) found that latencies for two tasks, matching judgment and phoneme identification in quiet, were negatively affected by variability in emotional prosody, suggesting that listeners benefit from repeated presentation of the same emotions. Mullennix et al (2002) found that latencies for two tasks, matching judgment and phoneme identification in quiet, were negatively affected by variability in emotional prosody, suggesting that listeners benefit from repeated presentation of the same emotions.…”
Section: Introductionmentioning
confidence: 95%